Synthesis of Nitric Oxide-Releasing Polyurethanes with S-Nitrosothiol-Containing Hard and Soft Segments - Coneski, Peter N. (2011)
Nitric oxide (NO)-releasing polyurethanes capable of releasing up to 0.20 μmol NO cm(−2) were synthesized by incorporating active S-nitrosothiol functionalities into hard and soft segment domains using thiol group protection and post-polymerization modifications, respectively. The nitrosothiol position within the hard and soft segment domains of the polyurethanes impacted both the total NO release and NO release kinetics. The NO storage and release properties were correlated to both chain extender modification and ensuing phase miscibility of the polyurethanes. Thorough material characterization is provided to examine the effects of hard and soft segment modifications on the resultant polyurethane properties.